2018
DOI: 10.1002/syn.22056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antinociceptive activities of several sodium channel blockers using veratrine test in mice

Abstract: An important role of voltage-gated sodium channels (VGSCs) in many different pain states has been established in animal models and humans wherein sodium channel blockers partially ameliorate pain. However, behavioral tests for screening analgesics that exhibit pharmacologic action by acting on VGSCs are rarely reported, and there are no studies on antinociception using veratrine as a nociceptive agent. The aim of the present study was to examine the amount of nociceptive behavior evoked by subcutaneous adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Despite its use over many decades, there still is no clear information on the mode of action of VPA at the molecular level. Proposed mechanisms have included effects on sodium channel-mediated currents, on GABA receptors, and the efficacy of excitatory neurotransmission (11)(12)(13)(14). Early studies on the administration of VPA to neuron cultures indicated its ability to modulate sodium and potassium ion conductance (15) and to modify sodium-dependent action potentials in neurons (16,17).…”
mentioning
confidence: 99%
“…Despite its use over many decades, there still is no clear information on the mode of action of VPA at the molecular level. Proposed mechanisms have included effects on sodium channel-mediated currents, on GABA receptors, and the efficacy of excitatory neurotransmission (11)(12)(13)(14). Early studies on the administration of VPA to neuron cultures indicated its ability to modulate sodium and potassium ion conductance (15) and to modify sodium-dependent action potentials in neurons (16,17).…”
mentioning
confidence: 99%
“…In our previous study, we demonstrated that mexiletine reduced the veratrine-induced nociceptive response in mice [9]. However, milnacipran may have difficulty binding to sodium channels because its planar structure is fixed by the cyclopropane structure [19].…”
Section: Discussionmentioning
confidence: 99%
“…The veratrine test was performed as described previously [9]. Veratrine solution of 40 µL (1.0 µg) was injected under the skin of the dorsal surface of the right hind paw using a microsyringe with a 30-gage needle.…”
Section: Veratrine Testmentioning
confidence: 99%
See 2 more Smart Citations